PERANAN STATUS GIZI SEBAGAI UPAYA PENCEGAHAN RISIKO STUNTING SEJAK MASA REMAJA MELALUI “GERMAS PEDULI STUNTING” DI DESA CADASKERTAJAYA KABUPATEN KARAWANG - Setiawati, Riska; Yanti, Irma; Apriningrum, Nelly; Sopiah, Oon; Wariah, Uway; Suryani, Lilis; Marlina, Rina; Alia Rahayu, Maria; Hamdayani, Irma; Nurlailasari, Ella (NHM PRESS, 2024)
Background: The direct factors of stunting are lack of nutritional intake and the presence of infectious diseases, while the indirect causes include maternal nutritional factors during adolescence, before, and during pregnancy, which can contribute to fetal growth, potentially resulting in a baby being born with malnutrition. Objective: Nutritional status is a variable in this research. This study aims to determine the role of nutritional status in stunting prevention by examining the relationship between education, behavior, and knowledge of young women. Method: This study is an observational analytical research using a cross-sectional design. The sample was selected using simple random sampling from all unmarried female teenagers aged 12-24 years, totaling 45 participants. Data were collected using a questionnaire. Results: The results showed that most of the BMI of female adolescents was in the normal category. Statistical tests indicated a p-value of 0.004, revealing a significant difference in the proportion of BMI between respondents with poor and good stunting prevention behaviors. A p-value of 0.652 indicated no significant difference in the proportion of BMI between respondents with poor and good knowledge of stunting prevention. Additionally, a p-value of 0.015 showed a significant difference in the proportion of BMI between respondents with primary and secondary education. Conclusion: Habits acquired during adolescence can have a significant impact on behavior. Increasing the knowledge of female adolescents should be further enhanced through health approaches and education.